Antiproliferative and anti-tyrosinase activities of propolis from tetragonula laeviceps and tetragonula pegdeni in Thailand - Thitipan Meemongkolkiat,; Songchan Puthong,; Phanthiwa Khongkarat,; Preecha Rod-Im,; Orawan Duangphakdee,; Preecha Phuwapraisirisan,; Chanpen Chanchao, (Universiti Kebangsaan Malaysia, 2023)
Propolis is one of the economic bee products with biological activities, but these activities can vary according to the local plants and bee species. This study aimed to evaluate the cytotoxic and antityrosinase activity of the methanol-, hexane-, and dichloromethane-partitioned propolis extracts (MPE, HPE, and DPE, respectively) of two dominant stingless bee species in Thailand (Tetragonula laeviceps and Tetragonula pegdeni) sourced from four locations in Ratchaburi province and one location in Chiangmai province. Their antiproliferative/cytotoxic activity, as the relative cell viability, was screened against the liver (Hep-G2) and gastric carcinoma (KATO-III) cancer cell lines in comparison to the untransformed lung fibroblast (WI-38) cell line using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay. Interestingly, DPE7 was the extract that showed great potential anticancer properties because it was significantly higher cytotoxic to cancer cell lines (Hep-G2 and KATO-III, with IC50 values of 36.40 and 35.15 μg/mL, respectively) than to normal cell lines (WI-38, with IC50 values of 46.52 μg/mL). Although DPE7 did not exhibit the highest antityrosinase activity, its moderate antityrosinase activity (IC50 of 1.388 mg/mL) considered it possible for further purification though not as effective as Kojic acid (IC50 of 0.0432 mg/mL). Besides, the different bioactivities in propolis from different sites were expected due to the different flora in each location. However, further studies are needed to better understand the properties and safety aspects of selected partitioned extracts.